Looking Around Flatland: End-to-End 2D Real-Time NLOS Imaging - Peña, María; Gutierrez, Diego; Marco, Julio (Jornada de Jóvenes Investigadores del I3A, 2025)
Non-line-of-sight (NLOS) imaging methods reconstruct scenes hidden around one corner using indirect third-bounce illumination with high temporal resolution on a visible surface. Unfortunately, acquiring or simulating this information is expensive. We present a simulation-based NLOS imaging pipeline for scenes with two spatial dimensions to enable fast prototyping and analysis.